(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. This study was conducted to determine the effect of statins on the serum levels of interleukin-6 (IL-6), low-density lipoprotein cholesterol (LDLC), and high-sensitivity C-reactive protein (HSCPR). Materials and Methods. This randomized clinical trial was carried out on 95 hemodialysis patients divided into three groups of atorvastatin, 10 mg; simvastatin, 20 mg; and lovastatin, 40 mg, daily, administered for 2 months. Levels of serum HSCRP, IL-6, and LDLC were all measured before and after the study period. Results. At baseline, 59% of the hemodialysis patients presented with elevated HSCRP, 46.3% them had increased IL-6, and 26.3% had an increased LDLC level. The three drugs were capable to lower the level of HSCRP, among which atorvastatin had the highest effect size (41.8% reduction, P = .001). Lovastatin stood in the next (37.6% reduction, P = .02), while HSCRP reduction was not significant in the simvastatin group (25% reduction, P = .14). Neither of the drugs significantly reduced IL-6 levels. Effects of atorvastatin and simvastatin on the LDLC levels were significant, while lovastatin had a marginal effect. Conclusions. Use of statins resulted in CRP reduction in patients on hemodialysis. Atorvastatin was much more effective than lovastatin, while CRP reduction was not significant by simvastatin. However, simvastatin had the greatest impact on LDLC. None of these drugs could reduce IL-6 levels within 2 months.